Amine Landscaping to Maximize Protein-Dye Fluorescence and Ultrastable Protein-Ligand Interaction. Issue 8 (17th August 2017) - Jacobsen, Michael T.; Fairhead, Michael; Fogelstrand, Per; Howarth, Mark
Summary: Chemical modification of proteins provides great opportunities to control and visualize living systems. The most common way to modify proteins is reaction of their abundant amines with N-hydroxysuccinimide (NHS) esters. Here we explore the impact of amine number and positioning on protein-conjugate behavior using streptavidin-biotin, a central research tool. Dye-NHS modification of streptavidin severely damaged ligand binding, necessitating development of a new streptavidin-retaining ultrastable binding after labeling. Exploring the ideal level of dye modification, we engineered a panel bearing 1–6 amines per subunit: "amine landscaping." Surprisingly, brightness increased as amine number decreased, revealing extensive quenching following conventional labeling. We ultimately selected Flavidin (fluorophore-friendly streptavidin), combining ultrastable ligand binding with increased brightness after conjugation. Flavidin enhanced fluorescent imaging, allowing more sensitive and specific cell labeling in tissues. Flavidin should have wide application in molecular detection, providing a general insight into how to optimize simultaneously the behavior of the biomolecule and the chemical probe. Graphical Abstract: Highlights: Labeling of streptavidin with small-molecule dyes impairs ligand binding K121R mutation rescues ligand stability after dye labeling Landscaping of protein amines optimizes brightness Fluorophore-friendly streptavidin improves imaging specificity and sensitivity Abstract : Chemical coupling of dyes frequently damages protein function. Jacobsen et al. explored this challenge using the widespread tool streptavidin. Through an amine-landscaping strategy, they produced "Fluorophore-friendly streptavidin" which combines extreme ligand-binding stability with brighter and more specific cellular imaging performance.